Environmental Care Education for Students of State Elementary School 105337 Pantai Labu Pekan - Ritonga, Zon Saroha; Emy Hariati; Nuri Ramadhan; Leni Malinda (Outline Journal of Community Development, 2025)
Tri Dharma of Higher Education is a concept that serves as a guideline for higher education institutions in carrying out their duties and functions. This concept consists of three pillars, namely: Education and teaching, Research and Community Service. Community service activities for lecturers are an effort to carry out one of the tasks of Tri Dharma of Higher Education. Community service carried out in this activity is regarding the Socialization of Environmental Care Education for Elementary School Students 105337 Pantai Labu Pekan located in Pantai Labu Pekan Village, Deli Serdang Regency. This activity aims to carry out the Tri Dharma of Higher Education activities for lecturers in order to contribute knowledge of social skills with sub-education to the community. The service carried out by several lecturers and students of the Nahdlatul Ulama University of North Sumatra (UNUSU) provides knowledge for the community in Pantai Labu Village so that they have an understanding of the importance of caring for the environment. It is hoped that students and the community in Pantai Labu Pekan Village understand the importance of environmental education. The expected output targets from this activity are: to provide knowledge to the community of Pantai Labu Pekan Village about the importance of environmental education